Bisphenol A (BPA) leading to obesity and cardiovascular complications: a compilation of current in vivo study - Naomi, Ruth; Yazid, Muhammad Dain; Bahari, Hasnah; Yong, Yoke Keong; Rajandram, Retnagowri; Embong, Hashim; Soo, Huat Teoh; Halim, Shariff; Othman, Fezah (MDPI, 2022)
BPA is one of the most common endocrine disruptors that is widely being manufactured daily nationwide. Although scientific evidence supports claims of negative effects of BPA on humans, there is also evidence suggesting that a low level of BPA is safe. However, numerous in vivo trials contraindicate with this claim and there is a high possibility of BPA exposure could lead to obesity. It has been speculated that this does not stop with the exposed subjects only, but may also cause transgenerational effects. Direct disruption of endocrine regulation, neuroimmune and signaling pathways, as well as gut microbiata, has been identified to be interrupted by BPA exposure, leading to overweight or obesity. In these instances, cardiovascular complications are one of the primary notable clinical signs. In regard to this claim, this review paper discusses the role of BPA on obesity in the perspective of endocrine disruptions and possible cardiovascular complications that may arise due to BPA. Thus, the aim of this review is to outline the changes in gut microbiota and neuroimmune or signaling mechanisms involved in obesity in relation to BPA. To identify potentially relevant articles, a depth search was done on the databases Nature, PubMed, Wiley Online Library, and Medline & Ovid from the past 5 years. According to Boolean operator guideline, selected keywords such as (1) BPA OR environmental chemical AND fat OR LDL OR obese AND transgenerational effects or phenocopy (2) Endocrine disruptors OR chemical AND lipodystrophy AND phenocopy (3) Lipid profile OR weight changes AND cardiovascular effect (4) BPA AND neuroimmune OR gene signaling, were used as search terms. Upon screening, 11 articles were finalized to be further reviewed and data extraction tables containing information on (1) the type of animal model (2) duration and dosage of BPA exposure (3) changes in the lipid profile or weight (4) genes, signaling mechanism, or any neuroimmune signal involved, and (5) transgenerational effects were created. In toto, the study indicates there are high chances of BPA exposure affecting lipid profile and gene associated with lipolysis, leading to obesity. Therefore, this scoping review recapitulates the possible effects of BPA that may lead to obesity with the evidence of current in vivo trials. The biomarkers, safety concerns, recommended dosage, and the impact of COVID-19 on BPA are also briefly described.